2010
DOI: 10.1111/j.1524-475x.2010.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of cutaneous wound healing by local application of mesenchymal stem cells derived from human umbilical cord blood

Abstract: This study aimed to determine whether mesenchymal stem cells (MSCs) derived from umbilical cord blood (UCB) would promote cutaneous wound healing. MSCs from human UCB were isolated and identified. The characteristics of the isolated MSCs' growth and proliferation were assayed in vitro. The MSCs labeled with 5-bromodeoxyuridine (BrdU) were applied on fresh cutaneous mice wounds. The healing rates were surveyed. The distribution and the differentiation into keratinocytes of the labeled MSCs in the wound tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 36 publications
5
87
1
3
Order By: Relevance
“…6,7 Recently MSCs have been shown to support cutaneous wound regeneration by accelerating wound closure, reducing scarring, and restoring the final tensilestrength of the tissue to levels higher than untreated wounds. [8][9][10][11][12][13][14] Also their well-documented immunomodulatory and anti-inflammatory properties 15 make these cells an attractive cell source for treating chronic wounds.…”
mentioning
confidence: 99%
“…6,7 Recently MSCs have been shown to support cutaneous wound regeneration by accelerating wound closure, reducing scarring, and restoring the final tensilestrength of the tissue to levels higher than untreated wounds. [8][9][10][11][12][13][14] Also their well-documented immunomodulatory and anti-inflammatory properties 15 make these cells an attractive cell source for treating chronic wounds.…”
mentioning
confidence: 99%
“…5 It has been observed that the local administration of Mesenchymal Stem Cells (MSCs) derived from Umbilical Cord Blood (UCB) improves skin wound healing in mice and it was found that the implanted MSCs could differentiate into keratinocytes in the wound. 6 We thought of using Human…”
Section: Discussionmentioning
confidence: 99%
“…hUC blood-derived MSCs enhanced wound healing in mice by differentiating into keratinocytes (Luo et al 2010). Although it is known that bone marrow-derived MSCs (BMSCs) will home to the injury sites and contribute to keratinocytes for skin regeneration in vivo after skin injury (Borue et al 2004;Satoh et al 2004;Badiavas et al 2003) and differentiate into epidermal lineage in 3D organotypic co-culture (Ma et al 2009), similar analyses have not been performed using hUCMSCs.…”
Section: Introductionmentioning
confidence: 99%